Long-term survival of patients with incomplete bundle-branch block complicating acute myocardial infarction. Issue 9 (September 1975) - Lichstein, E; Gupta, P K; Chadda, K D
Abstract : Electrocardiograms and His bundle electrograms were reviewed in 28 patients with incomplete bilateral bundle-branch block complicating acute myocardial infarction. All had a His bundle electrogram at the time of pacemaker insertion; 10 had a second one. Of 23 patients with an initially abnormal HV interval (55 ms or greater), 15 died (65%), while only one died (20%) in the group of 5 with a normal HV interval. This difference is not statistically significant. Sequential His bundle electrograms were done in 6 of the 8 survivors with an initially abnormal HV interval, and 4 showed 10 to 15 ms decrease in HV interval. The disappearance of incomplete bilateral bundle-branch block occurred significantly more often in patients who survived (7 of 12) when compared with those who did not survive (2 of 16) (P less than 0.05). It is concluded that long-term survival is po-sible after incomplete bilateral bundle-branch block complicating acute myocardial infarction. The characteristics of the survivors include an initially normal HV interval, transient incomplete belateral bundle-branch block and a decreasing HV interval if it were initially abnormal.